Effects of the location of the nanoclay at the interface on the mechanical properties of a maleic anhydride grafted polypropylene/polyamide 6/organoclay co-continuous blend - Goitisolo, Izaro; González, Imanol; Eguiazábal, José Ignacio (Polymers for advanced technologies, 2013)
The effects of the location at the interface of an organoclay on the morphology and mechanical properties of a maleated‐polypropylene/polyamide 6 based co‐continuous blend have been studied. The organoclay is located at the interface because the level of interaction with each of the two polymers was similar. The dispersed particle size remained unchanged with organoclay content because the effect of viscosity and coalescence inhibition was offset by the surfactant compatibilization hindering. The Young's modulus remained constant; this behavior is mainly attributed to the inefficient orientation of the nanoclay. The ductility behavior suggests that there is a maximum amount of organoclay that can be located at the interface while retaining its ductile nature. Once this amount has been exceeded, the interface becomes saturated, and the dispersed particles become encapsulated. Encapsulation means that both an inorganic barrier and discontinuity appear, hindering the stress transmission through the interface and leading to fragility. Copyright © 2012 John Wiley & Sons, Ltd.